Contouring lumbosacral plexus nerves with MR neurography and MR/CT deformable registration technique - Cao, Xi; Gao, Xian-Shu; Li, Wei; Liu, Peilin; Qin, Shang-Bin; Dou, Yan-Bin; Li, Hong-Zhen; Shang, Shiyu; Gu, Xiao-Bin; Ma, Ming-Wei; Qi, Xin; Xie, Mu; et al. (Frontiers in Oncology, 2022)
Purpose: It is difficult to contour the nerve structures with the naked eye due to poor differentiation between the nerve structure with other soft tissue on CT images. Magnetic resonance neurography (MRN) has the advantage in nerve visualization. The purpose of this study is to identify one MRN sequence to better assist delineation of the lumbosacral plexus (LSP) nerves to assess radiation dose to the LSP using MR/CT deformable co-registration technique. Methods: Eighteen cases of prostate cancer patients and one volunteer with radiation-induced lumbosacral plexopathy (RILSP) were enrolled. Data of simulation CT images and original treatment plans were collected. Two MRN sequences (the Lr_NerveVIEW sequence and the Cs_NerveVIEW sequence) were optimized from a published MRN sequence (3D NerveVIEW sequence). The nerve visualization ability of the Lr_NerveVIEW sequence and the Cs_NerveVIEW sequence was evaluated via a four-point nerve visualization score (NVS) scale in the first ten patients enrolled, to determine the better MRN sequence for assisting nerve contouring. Deformable registration was applied to the selected MRN sequence and simulation CT images to get fused MR/CT images, on which the LSP was delineated. The contouring of LSP did not alter treatment planning. Dosimetric data of the LSP nerve were collected from the dose-volume histogram in the original treatment plans. Data of the maximal dose (Dmax) and the location of maximal radiation point received by the LSP structures were collected. Results: Lr_NerveVIEW sequence gained higher NVS scores than Cs_NerveVIEW sequence (Z=-2.887, p=0.004). The LSP structures were successfully created in 18 patients and 1 volunteer with MRN (Lr_NerveVIEW)/CT deformable registration techniques, and the LSP structures conformed with the anatomic distribution. In the patient cohort, the percentage of LSP receiving doses exceeding 50 Gy, 55 Gy and 60 Gy was 68% (12/18), 33% (6/18) and 17% (3/18), respectively. For the volunteer with RILSP, the maximum irradiation dose to his LSP nerves was 69Gy. Conclusion: Lr_NerveVIEW MRN sequence performed better than the Cs_NerveVIEW sequence in nerve visualization. Dose in LSP needs to be measured to understand the potential impact on treatment-induced neuropathy.